Serum glucose, sodium and potassium concentrations in patients with diabetic ketoacidosis - Željka Dragila; Dora Rudić; Klara Ćosić; Tatjana Bačun (Medicinski glasnik, 2022)
Aim: To investigate possible differences in serum glucose and sodium and potassium concentrations with respect to age, gender and severity of diabetic ketoacidosis. Methods: Medical records from 1 January 2017 to 31 December 2019 were reviewed and patients with the diagnosis of diabetic ketoacidosis were selected. Results: The study included 52 patients. Glucose concentration was significantly higher in the age group of 25-44 and >65 years compared to the group of 18-24 years (p=0.02). Sodium concentration was significantly higher in the age group 18-24 and >65 years compared to groups 25-44 and 45-65 years (p=0.002). Females had significantly higher sodium concentration than males (p=0.002). Potassium concentration was significantly higher in the age group 25-44 years compared to other groups (p=0.01). Males had significantly higher potassium concentration (p =0.01). Conclusion: This study showed that significant differences exist in electrolyte concentration between specific age groups, male and female gender as well as DKA severity. Knowing these differences could help clinicians to promptly recognize and treat electrolyte derangements, leading to better outcome of patients with DKA.
Keywords: diabetes complication; electrolyte; emergency medicine; hyperglycemia